The Ethics of Self-Management Preparation for Chronic Illness - Redman, Barbara K (Nursing ethics, 2005)
While nearly all patients with a chronic disease must self-manage their condition to some extent, preparation for these responsibilities is infrequently assured in the USA. The result can be significant harm and the undermining of a patient’s ability to take advantage of life opportunities and be productive. Agreeing to care for a patient involves a moral responsibility to see that she or he receives the essential elements of care, including the ability to manage the disease on a daily basis. The research base for the efficacy of self-management and for how patients can be prepared to assume it is sufficiently strong that health care professionals must advocate for its inclusion in the routine evidence-based care of individuals with chronic disease. Because patient education is central to nursing’s philosophy and practice, the profession should play a major role in removing structural barriers to self-management preparation and assuring its provision to a high standard of quality.